The evaluation of institutional reforms at subnational government levels: A still neglected research agenda - Kuhlmann, Sabine; Wollmann, Hellmut (2011)
This article is meant to take a noteworthy step towards conceptually promoting the evaluation of institutional reform policies in the sub-national space. It aims to apply pertinent approaches of evaluation to the field of institutional reform policies in the intergovernmental setting and thus to contribute to a research field that arguably has so far been a 'missing link' in policy evaluation. The authors conceptualise institutional policies (territorial and functional reforms) as a particular type of public policy and contrast them analytically, conceptually and methodologically with 'normal' substantial policies. They reveal particular problems of measurement and of finding relevant indicators to evaluate theresults of institutional reforms, one of which is the assessment of the transaction costs of reforms. Finally, an analytical framework for the evaluation of functional and territorial reform policies is suggested that makes a distinction between 'institution evaluation' and 'performance evaluation', and that can be applied in comparative evaluation studies. - Reproduced.
Keywords: Organizations